(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
It is difficult to find a person in the Old Testament who is regarded as extreme as Balaam. Despite the conclusion in Numbers says he went back to his hometown after blessing Israel in chapters 22-24, most other passages of the Old Testament view him in highly unfavorable light. Although Balaam’s name is not mentioned in the crime of fornication with Moabite women in Shittim, Numbers 31 records that the Israelites’ sin in Shittim was attributable to the "counsel of Balaam," which resulted in the death of Balaam. Studies on Balaam and the Balaam narrative have advanced significantly, although they have mainly focused on positive or negative evaluations of Balaam and historical studies based on the name contained in the Deir ’Alla Inscription. This study intends to start from the point that Balaam was the first Gentile to receive the ‘Spirit of God’ in the Old Testament. The Spirit of God is a symbol of the unseen presence that replaces the temple in the Old Testament, and the anointing of the Spirit is a typical post-exilic style used as a method of selecting people to accomplish God’s work in lieu of the anointing. The fact that Gentile was used as God’s prophet reflects the idea of universalism that appeared in the latter days of the Post-Exilic Period.